2013
DOI: 10.1111/jdv.12297
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume is associated with aortic arterial stiffness in patients with Behçet's disease without significant cardiovascular involvement

Abstract: In our study, increased MPV is associated with arterial stiffness in patients with BD without significant cardiovascular involvement. It shows that there is a relationship between thrombosis and chronic inflammation in BD. Furthermore, MPV is also a moderate predictor of cardiovascular disease and represents an increase in platelet activation. These findings provide further evidence of a link between inflammation and thrombosis in patients with BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 34 publications
1
39
2
1
Order By: Relevance
“…As a meta‐analysis comprising 24 trials demonstrated, MPV is a positively associated with incidence of myocardial infarction as well as restenosis after coronary angioplasty (Chu et al, 2010). Meanwhile, high MPV levels had been found in patients with aortic arterial stiffness, peripheral artery disease (Balta et al, 2014; Berger, Eraso, Xie, Sha, & Mohler, 2010). Previous studies reported that high MPV levels were correlated with increased risk of ischemic stroke as well as unfavorable prognosis among survivors of stroke (Bath, Algert, Chapman, & Neal, 2004; Muscari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As a meta‐analysis comprising 24 trials demonstrated, MPV is a positively associated with incidence of myocardial infarction as well as restenosis after coronary angioplasty (Chu et al, 2010). Meanwhile, high MPV levels had been found in patients with aortic arterial stiffness, peripheral artery disease (Balta et al, 2014; Berger, Eraso, Xie, Sha, & Mohler, 2010). Previous studies reported that high MPV levels were correlated with increased risk of ischemic stroke as well as unfavorable prognosis among survivors of stroke (Bath, Algert, Chapman, & Neal, 2004; Muscari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…4 Endothelial dysfunction (ED) is also considered to play an important role in the pathogenesis of vasculitis and thrombosis in BD. 5 Vascular involvement affects veins and arteries of all sizes and is more frequent and has a more severe course in young males. 6 Several markers can be used to evaluate ED and vascular involvement in BD (eg, mean platelet volume, 7 neutrophil-lymphocyte ratio, 8 red cell distribution width, 9 g-glutamyl transferase activity, 10 and uric acid levels 11 ).…”
mentioning
confidence: 99%
“…18 Increased AS may be attributed to ED and inflammation associated with BD. 5 The hsCRP reflects systemic inflammation and is related to ED. 16,[18][19][20][21][22][23][24] These findings as well as coagulation and fibrinolytic abnormalities may contribute to ED in BD.…”
mentioning
confidence: 99%
“…2 Larger platelets are known to be denser, and those platelets are associated with increased thrombogenesis in various cardiovascular diseases. [3][4][5][6][7] Platelets play an important role in the pathogenesis of acute coronary syndromes (ACSs). 8 A larger platelet volume is associated with enhanced platelet reactivity.…”
mentioning
confidence: 99%